2017
DOI: 10.1097/jcn.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangements Modify the Relationship Between Depressive Symptoms and Self-care in Patients With Heart Failure

Abstract: Background: Depressive symptoms hinder heart failure patients’ engagement in self-care. As social support helps improve self-care and decrease depressive symptoms, it is possible that social support buffers the negative impact of depressive symptoms on self-care. Objective: The purpose of this study is to examine the effect of living arrangements as an indicator of social support on the relationship between depressive symptoms and self-care in heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…Research has shown that the experience of having symptoms can motivate chronically ill individuals to perform self-care 32. However, depressive symptoms and cognitive decline can blunt self-care by decreasing motivation to engage in healthy behaviors 4547…”
Section: Proposing a Revision Of The Middle-range Theory Integrating mentioning
confidence: 99%
“…Research has shown that the experience of having symptoms can motivate chronically ill individuals to perform self-care 32. However, depressive symptoms and cognitive decline can blunt self-care by decreasing motivation to engage in healthy behaviors 4547…”
Section: Proposing a Revision Of The Middle-range Theory Integrating mentioning
confidence: 99%
“…Depression and depressive symptoms are associated with poor self‐care in those with CVD or risk factors for CVD . Self‐care areas negatively affected include diet and medication adherence, exercise adherence, self‐monitoring, and appropriate response to symptoms …”
Section: Factors Influencing Self‐carementioning
confidence: 99%
“…Studies conducted on self‐care in other chronic conditions have found that being employed (Ausili et al., 2018) or unemployed (Cocchieri et al., 2015), education level (Ausili et al., 2018), caregiver support (Cocchieri et al., 2015) and living alone (Lee, Lennie, Yoon, Wu, & Moser, 2017) can influence self‐care, but these variables have never been investigated in ostomy self‐care. Regarding income, no significant relationship has been found between ostomy self‐care and income (Bulkley et al., 2018).…”
Section: Introductionmentioning
confidence: 99%